Leaving and Entering Religion:Understanding Religious Conversion in the Discourse of Religious Freedom and Human Right - Paais, Vikry Reinaldo (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
Religious conversion is a problematic phenomenon. It is supported based on religious freedom, but opposed based on religious doctrines and truth claims. The debate on religious conversion in relation to freedom of religion or belief (FoRB) tends to stop on the dichotomy of universalism and relativism of human rights. That is, religious conversion is recognized as a universal value, but in a particular context became relative. In this perspective, the implementation of religious conversion, which should be universal, becomes limited. As a result, there are various kinds of stigmatization against the subjects of religious conversion, for instance, they are labeled as